Hubungan Preeklampsia Terhadap Kejadian Depresi Postpartum: Literature Review - Syifa, Faidana Yaumil (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to determine the relationship between preeclampsia and the incidence of postpartum depression in postpartum mothers.. Methods: The research method used in this study is a literature review. The electronic database used in the article search is PubMed, Emerald Insight, Sage Journal and Science Direct. The selected articles are English articles with a time span of 2020-2025, and free full text. The selected articles are quantitative articles. The keywords used are (1) postpartum women, (2) women with preeclampsia, and (3) women with postpartum depression. Results: The results of searching for articles in electronic databases using keywords obtained 1,701 articles. Details of the search results for each electronic database are PubMed (n=113), Emerald insight (n=8), Sage journal (n=0) and Science direct (n=1,580). The articles were selected by identifying articles based on keywords (n=13). The next step, articles were identified based on accessible articles (n=6). The final step is to identify articles based on abstract suitability (n=6). Conclusion: There is a relationship between preeclampsia and the incidence of postpartum depression. Preeclampsia can occur from early pregnancy to the 12th week postpartum. The role of the family, health workers, society and even mothers (patients) to pay more attention and care about maternal health because physical health (preeclampsia) and psychological health are related to each other.